ANALISIS PENGARUH DEBIT AIR TERHADAP KINERJA PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - OLOAN OKI NAWA (LPPM Politeknik LP3I Medan, 2021)
Electricity is one of the sources of energy used by humans which is produced through a power generation system. Electricity providers in Indonesia are still not evenly distributed, even in remote areas, there are still many that have not been reached by electricity. With this problem, one of the renewable power plants that can be utilized is the PLTMH system (Microhydro Power Plant). The greater the discharge of water, the greater the power generated by the turbine but with a shorter time. Vice versa if the water discharge that comes out is less then the power generated by the turbine is getting smaller but with a long time. The results show a whirlpool turbine using 6 blades with a water volume of 58 L and a sluice gate opening 7 cm produces a water discharge of 0.00625 m3/s with Water Power 14.10 Watt, , Generator Power 11.12, Torque 0.0077N.m, Turbine Power 0.72 Watt and Efficiency 5.1%.